Dinamika Dakwah Melalui Buletin: Studi Perkembangan Lembaga Islamic Thought and Information for Dakwah (ISTAID) Center Medan, 2019-2021 - Malik, Maulana; Siregar, Yusra Dewi; Yasmin, Nabila (Local History & Heritage, 2024)
This study examines the development of the ISTAID Center, an Islamic institution in Medan that has consistently distributed bulletins since 1993. The research aims to provide a comprehensive understanding of the institutional changes at ISTAID by tracing its historical development and analyzing the social phenomena reflected in its newsletters. Specifically, the focus is on the period from 2019-2021, exploring the central themes discussed in the bulletins. To investigate these dynamics, the research employs historical methods, including heuristics, verification, interpretation, and historiography, complemented by descriptive analysis of the bulletin content. Data collection involved primary sources from newsletters and interviews, supplemented by secondary sources. Wilhelm Dilthey's hermeneutic theory was applied to analyze thematic relevance within social contexts. The findings suggest that the ISTAID Center has played a significant role in reflecting and addressing the social situation of Muslims during the specified period, as evidenced through the thematic content of its bulletins.